Clostridioides difficile Infection in Children With Inflammatory Bowel Disease. Issue 11 (25th November 2019) - Chandrakumar, Abin; Zohni, Hussein; El-Matary, Wael
Abstract: Background: The study's objective was to investigate the incidence and risk factors associated with Clostridioides difficile (previously known as Clostridium ) infection (CDI) in children with inflammatory bowel disease (IBD) in the province of Manitoba. Methods: Our longitudinal population-based cohort was comprised of all children and young adults aged <17 years diagnosed with IBD in the Canadian province of Manitoba between 2011 and 2019. The diagnosis of CDI was confirmed based on the Triage C. difficile immunoassay and polymerase chain reaction assay to detect the presence of toxigenic C. difficile . The Fisher exact test was used to examine the relationship between categorical variables. A Cox regression model was used to estimate the risk of CDI development in IBD patients. Results: Among 261 children with IBD, 20 (7.7%) developed CDI with an incidence rate of 5.04 cases per 1000 person-years, and the median age at diagnosis (interquartile range) was 12.96 (9.33–15.81) years. The incidence rates of CDI among UC and CD patients were 4.16 cases per 1000 person-years and 5.88 cases per 1000 person-years, respectively ( P = 0.46). Compared with children without CDI, those who had CDI were at increased risk of future exposure to systemic corticosteroids (adjusted hazard ratio [aHR], 4.38; 95% confidence interval [CI], 1.46–13.10) and anti–tumor necrosis factor (anti-TNF) biologics (aHR, 3.31; 95% CI, 1.11–9.90). The recurrence rate of CDI in our pediatric IBD population was 25%. Conclusions: Our findings confirm that children with IBD are at high risk of developing CDI, which may predict future escalation of IBD therapy.